Non-menstrual pelvic symptoms and women's quality of life: a cross-sectional observational study. - Marlon de Freitas Fonseca; Felipe Ventura Sessa; Claudio Peixoto Crispi; Nilton de Nadai Filho; Bruna Rafaela Santos de Oliveira; Rafael Ferreira Garcia; Claudio Peixoto Crispi (PLoS ONE)
Background Endometriosis-related pain duration and burden are associated with poorer psychological well-being and health-related quality of life (HQoLife). This study aimed to compare the relative burdens of 4 different non-menstrual pelvic symptoms on HQoLife: Deep dyspareunia (DDyspareunia), non-menstrual pelvic pain (NMPelvicPain), non-menstrual dyschezia (NMDyschezia) and non-menstrual dysuria (NMDysuria). Subjects and methods This is a pre-planned cross-sectional interdisciplinary retrospective observational study. The sample consists of 369 consecutive patients referred for minimally invasive surgery at a private institution. DDyspareunia, NMPelvicPain, NMDyschezia and NMDysuria were assessed with a self-reported 11-point (0-10) numeric rating scale (NRS). The Short Form 36 (SF36) and Endometriosis Health Profile 30 (EHP30) full questionnaires were applied to assess HQoLife. Multiple linear regression models were used to compare the 4 explanatory variables (correlates), which were tested for 19 different HQoLife domains. Results Multivariate exploratory analyses indicated that NMPelvicPain and NMDyschezia may be the non-menstrual pelvic symptoms that most impact the HQoLife of women with endometriosis, an association that was observed in practically all domains of both the SF36 and the EHP30 questionnaires. DDyspareunia was the most important symptom for the sexual intercourse EHP30 domain. Despite the biological plausibility and statistical significance found in virtually all models, their low explanatory power suggests the existence of additional major covariates (not contemplated in this study). Moreover, the presence of significant positive intercepts (P<0.001) implies that some HQoLife impairment is expected for any hypothetical woman with endometriosis, even if all 4 correlates' scores are equal to zero. Our findings support the hypothesis that the importance of bowel symptoms has been underestimated in endometriosis assessment whereas the burden of other potential covariates should not be neglected. Conclusion DDyspareunia was the most important non-menstrual pelvic symptoms for the EHP30Sex domain, but NMPelvic Pain and NMDyschezia were the most important for overall HQoLife.